Детский фразеологический словарь в картинках - Волков Сергей Владимирович (АСТ:Астрель, 2010)
Экземпляры: (20111014) / Инвентарный номер: 47195 / Цена: 173.52 / Сис.шифр: 81.2Рус-ср. / Авт.знак: В 67 / ББК: 81.2Рус-ср.